S49 A Self-Management Programme of Activity Coping and Education (SPACE) For COPD: Results from a Randomised Controlled Trial. (19th November 2012) - Mitchell-Wagg, K; Warrington, V; Apps, L; Sewell, L; Bankart, J; Steiner, M; Morgan, M; Singh, S; Singh, S
Abstract : Introduction: The NHS Outcomes Strategy for COPD has identified self-management as an approach targeted at reducing the impact of COPD. 1 Previous self-management programmes have either been unsupported, such as brief education or action plans, or have been of high intensity, equivalent with pulmonary rehabilitation. Furthermore, no studies have specifically tested self-management in patients managed in primary care. SPACE is a supported self-management programme that adopts a light touch approach. This study aimed to test the effectiveness of SPACE in patients with COPD in primary care. Methods: 184 patients [101 male; mean (SD) age 69 (9) yrs; FEV11.44 (0.56) l; BMI 27.56 (5.26) kg/m2] with COPD were recruited and randomised to either SPACE or usual care. Patients who received SPACE were introduced to a manual by a healthcare professional and received two telephone calls at 2 and 4 weeks. Measures were taken at baseline, 6 weeks and 6 months. The primary outcome was the Chronic Respiratory Questionnaire (CRQ) dyspnoea. Secondary outcomes were CRQ fatigue, emotion and mastery, Incremental Shuttle Walk Test (ISWT), Endurance Shuttle Walk Test (ESWT) and Hospital Anxiety and Depression Scale (HADS). HADS was analysed on a sub-group of those scoring ≥8 at baseline. Repeated measures ANOVA was conducted to test the effect of time and intervention. Results Results: are displayed in table 1 . Conclusions: SPACE can bring about gains in HRQoL, endurance capacity and reduced depression for those at risk, that are maintained over 6 months. These are important patient outcomes which suggest self-management skills of emotional and medical management have been gained. Reference: Department of Health. 'An Outcomes Strategy for COPD and Asthma: NHS Companion Document.' May 2012.